Hydrogen‐bonding assembly of heteropolyacid and poly(vinyl alcohol) for strong, flexible, and transparent UV‐protective films. Issue 24 (16th December 2019) - Zhang, Ziang; Chen, Kui; Tang, Qun; Li, Heping; Zou, Zhiming
ABSTRACT: Although many preparation approaches have been developed, it remains a huge challenge to achieve ultraviolet (UV)‐protection films that combine high transparency, excellent UV‐shielding, and mechanical properties. Herein, we demonstrate a facile and eco‐friendly process for fabricating strong, flexible, and transparent UV‐protective poly(vinyl alcohol) (PVA) films by exploiting silicomolybdic acid (SiMoA) as UV absorber and reinforcing phase. Fourier‐transform infrared analysis confirms the formation of strong hydrogen‐bonding interactions between PVA and SiMoA. The glass‐transition temperature, mechanical properties, and UV‐shielding stability of the UV‐protective PVA composite films obviously increase with increasing the content of SiMoA. By incorporation of only 2 wt % SiMoA, the UV‐protective PVA composite film can block more than 90% of UV light in the entire UV regions and retain high visible light transparency (up to 95%). Simultaneously, the UV‐protective PVA composite film presents excellent mechanical properties with a tensile strength of 65.2 MPa and an elongation at break of 172.6%, which are 72.0 and 69.5% higher than that of pristine PVA films. This work provides a simple but effective approach for creating strong, flexible, and transparent UV‐blocking polymeric materials via hydrogen‐bonding assembly, which are expected to have wide application prospects in UV‐protection field. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48813. Abstract :